Evaluation of polyphenolic content and antioxidant activity in two onion varieties grown under organic and conventional production systems. (12th January 2017) - Ren, Feiyue; Reilly, Kim; Gaffney, Michael; Kerry, Joseph P; Hossain, Mohammad; Rai, Dilip K
Abstract: BACKGROUND: Onions contain a number of bioactive compounds, in particular polyphenols. They are rich sources of such compounds in the human diet and offer significant health benefits to the consumer. Demand for organic crops is steadily increasing partly based on the expected health benefits of organic food consumption. The current study examines the influence of organic and conventional crop management practices on bioactive polyphenolic content of onion. RESULTS: We examined the effect of conventional, organic, and mixed cultivation practices on the content of total phenolics, total flavonoids and antioxidant activity in two varieties of onion grown over 4 years in a split‐plot factorial systems comparison trial. Levels of total phenolics and total flavonoids showed a significant year‐on‐year variation and were significantly different between organic and conventional production systems. The levels of total phenolics, total flavonoids and antioxidant activity in general were significantly higher ( P < 0.05) under fully organic compared to fully conventional management. CONCLUSION: Organic cultivation practices resulted in significantly higher levels of potential bioactive compounds in onion. © 2016 Society of Chemical Industry